Local Biomass Processing is Practical for Facilitating Fermentation to Bioethanol - Savarese, John J. (Journal of Technology Innovations in Renewable Energy, 2013)
Local processing of biomass prior to fermentation at another site has advantages in transportation savings and in fermentation facility operation. To evaluate the feasibility of treating biomass locally to produce fermentation ready glucose an alkali-cellulase process was evaluated at laboratory scale using 5 g of three types of biomass. After pretreatment with an aqueous solution of NaOH (0.5% w/v, 20% w/w-biomass), T=100°C x 12 h, corn stover and wheat straw were shown to undergo cellulase hydrolysis to glucose; however, pine chips were not as susceptible. Commercially available cellulase was capable of producing glucose within three hours from corn stover and wheat straw. The NaOH pretreated biomass was mixed with enzymes in a small volume (50 mL) to conserve water. However, glucose inhibition of cellulase appeared to limit hydrolysis. Volume expansion by ten-fold dilution (500 mL) resulted in rapid release of glucose presumably by decreasing end product inhibition. Application at a commercial level will require increased water management. The resulting glucose solution could be concentrated by thermal or membrane technology for delivery to grain fermenting facilities to be used without further processing. Solids remaining after enzyme hydrolysis can be recycled locally to produce additional glucose. Scale-up of this alkali-cellulase process for local application appears feasible given the materials and conditions evaluated in this study. Local treatment of biomass using the alkali-cellulase process to produce glucose to be transported to existing grain fermenting facilities is a novel approach based on reliable technology and has been demonstrated at laboratory scale.